Ekosistem Inovasi sebagai Determinan Sustaining Innovation Layanan Publik Digital di Pemerintah Daerah (Studi Kasus SmartEdu di Kota Padang Panjang) - Zahara Erita; Boni Saputra (Policy, Law and Political Research Center, 2026)
This study aims to analyze the role of the organizational innovation ecosystem as a determinant of sustaining innovation in the SmartEdu digital public service at the Padang Panjang City Education and Culture Office. The method used is descriptive qualitative, with data collection through in-depth interviews and documentation. This study involved 17 informants consisting of the Head of the Office, Division Heads, office staff, school principals, school operators, and parents. Data analysis was conducted through data reduction, data presentation, and drawing conclusions. The research findings indicate that the sustainability of SmartEdu is determined by the synergy of four strategic factors within the innovation ecosystem: leadership commitment manifested through budgetary support and active oversight; a tiered innovation ecosystem with a strong legal foundation; the capacity and willingness to innovate through the collective strengthening of human resources; and the application of the “Think Like a Corporate University” principle through continuous evaluation and knowledge sharing. This research implies the need to institutionalize the innovation ecosystem within regional policies as a guarantee of the sustainability of responsive, inclusive, and accountable digital public services.